Characterizing the Effect of Arginine Deprivation on Autophagic Response in Breast Cancer cells - Haidar, Fatemah (2021)
The metabolism of arginine, a semi-essential amino acid, is required for homeostasis and deregulated in various diseases. When deprived of arginine, several types of cancers can modulate arginine synthesis mediated by the enzyme ASS1 or employ broader response mechanisms such as autophagy. The co-regulation of arginine metabolism and autophagy in breast cancer is poorly understood. In this project, we first inspected ASS-1 expression in human breast cancer patients and found that it decreases progressively with tumorigenesis and metastasis. Residual ASS1 tumor expression corelated with increased metastasis and decreased survival in patient luminal A, Her2+ and triple-negative breast cancer. We then utilize a pharmacological-grade formulation of human recombinant arginase (HuArgI(Co)-PEG5000) to characterize the effect of arginine deprivation in one luminal (MCF-7) and two triple negative (MDA-MB-231 and UACC-2087) models of breast cancer. Western blot analysis revealed that arginine deprivation was not sufficient to trigger a compensatory upregulation of ASS1 expression in any of the tested cell lines. However, arginine deprivation induced varying autophagic response in MCF-7, MDA-MB-231 and UACC-2087. Altogether, our findings suggest that the activation of autophagy could be a plausible mechanism for breast cancer cells to overcome arginine depletion. Future functional studies will reveal whether HuArgI(Co)-PEG5000-induced autophagy sustains long-term cancer cell survival, and whether combination with autophagy inhibitors constitutes a viable therapeutic strategy in breast cancer.